Discovery and Biosynthetic Investigation of a New Antibacterial Dehydrated Non‐Ribosomal Tripeptide. Issue 6 (11th December 2020) - Wang, Shan; Fang, Qing; Lu, Zhou; Gao, Yingli; Trembleau, Laurent; Ebel, Rainer; Andersen, Jeanette H.; Philips, Carol; Law, Samantha; Deng, Hai
Abstract: Dehydroalanine (Dha) and dehydrobutyrine (Dhb) display considerable flexibility in a variety of chemical and biological reactions. Natural products containing Dha and/or Dhb residues are often found to display diverse biological activities. While the ( Z ) geometry is predominant in nature, only a handful of metabolites containing ( E )‐Dhb have been found thus far. Here we report discovery of a new antimicrobial peptide, albopeptide, through NMR analysis and chemical synthesis, which contains two contiguous unsaturated residues, Dha‐( E )‐Dhb. It displays narrow‐spectrum activity against vancomycin‐resistant Enterococcus faecium . In‐vitro biochemical assays show that albopeptide originates from a noncanonical NRPS pathway featuring dehydration processes and catalysed by unusual condensation domains. Finally, we provide evidence of the occurrence of a previously untapped group of short unsaturated peptides in the bacterial kingdom, suggesting an important biological function in bacteria. Abstract : Albopeptide, a new antibacterial short peptidyl metabolite, was found to contain a unique contiguous Dha‐( E )‐Dhb moiety. In‐vitro reconstitution and biochemical analysis together with chemical capture of online biosynthetic intermediates demonstrated that two condensation domains in the corresponding NRPSs catalyse the dehydration reactions on the Ser and Thr residues, respectively, to generate Dha and ( E )‐Dhb residues.